Relationship of psychosocial stimulation by mother to development children age 3th-5 th years in Gamping 1st Public Health Center Working Area - Amelia, Ayu Pramestya; Dian Ayuningrum, Lia; Dwiarini, Muafiqoh (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2023)
Background: According to World The Health Organization (WHO) states that around 95% of children with developmental disorders live in the country income low and intermediate. Several studies show that stunting and being underweight are related to child development, especially motoric, cognitive, and language development on child. Psychosocial stimulation is external or environmental stimulation that is important for child development. Children who receive targeted and regular stimulation develop faster than children who receive less or no stimulation. If developmental deviations are not treated early and adequately, they tend to result in disability. Objectives: To determine the relationship between maternal psychosocial stimulation and children development age 3th– 5th years in Gamping 1st Public Health Center Working Area.Methods: The quantitative analytical research with design cross sectional. The sampling technique used is probability sampling with a type of cluster random sampling technique design with a total sample of 103 children from 1,421 in population at posyandu in Gamping 1st Public Health Center Working Area. Child development is measured using a Questionnaire Pre-Screening Development (KPSP). Psychosocial stimulation mothers were measured using the HOME instrument which has been tested by CVI Expert. The bivariate analysis used is the test chi square .Results: Based on the research results after carrying out the Chi Square Test, the p value was 0.002  (p-value was <0.05). Conclusions: That psychosocial stimulation has an relationship on children's development aged 3-5 years this is also one of the nurturing patterns that mothers can do at home. The need for further research is to control the amount or how much influence from outside regarding the information obtained by the mother which can influence the level or model of stimulation that the mother develops when providing stimulation